Reduction of dinitrotoluene by hydrated electrons generated from UV irradiation of toluene in wastewater: Towards cleaner production. (20th November 2019) - Akbari, Abbas; Sadani, Mohsen; Sedighizadeh, Alireza; Sedghi, Asieh; Khajeh, Mehdi; Mahmoudi, Mohsen; Bagheri, Amin; Teimouri, Fahimeh; Behin, Jamshid
Abstract: This study presents a sustainable approach for degrading dinitrotoluene to diaminotoluene in wastewater without the production of a secondary pollutant, to achieve cleaner production. This process eliminates the chemical oxygen demand of the pre-treated wastewater and ensures that the treated wastewater is reusable. In this study, the hydrated electron generated from the toluene/UV process at 254 nm in simulated wastewater, and the mechanism of its production were investigated. This mechanism demonstrated that intermediate benzyl radicals can continuously facilitate the generation of hydrated electrons by absorbing two photons during the UV process. In addition, the hydrated electron production via the photolysis of toluene resulted from the triplet state via a biphotonic process. To detect the hydrated electrons in aqueous solution, monochloroacetic acid and chloroethanol were applied. By studying the operating parameters, it was revealed that the hydrated electron generation efficiency was pH dependent, and the complete degradation of dinitrotoluene was achieved at an optimum pH of 7.5. Furthermore, the elimination of the remaining chemical oxygen demand related to the reduction process in simulated wastewater was investigated using heat-activated persulfate; through this advanced oxidation process, the chemical oxygen demand was almost completely eliminated. Depending on the pH and the model solution based on the wastewater composition, the proposed treatment technique, which is novel and environmentally friendly, can be applied to large-scale plants. Graphical abstract: Image 106501 Highlights: Establishing a practical technique to degrade dinitrotoluene to a cleaner production. Hydrated electrons were efficiently generated from Toluene/UV process. Toluene/UV process was performed at a neutral pH. Three validation tests were used to detect the production of hydrated electrons. A possible pathway of hydrated electrons generation was proposed.